Do Subliminal Fearful Facial Expressions Capture Attention? - Baier, Diane; Kempkes, Marleen; Ditye, Thomas; Ansorge, Ulrich (Frontiers in Psychology, 2022)
In two experiments, we tested if fearful facial expressions capture attention in an awareness-independent fashion. In Experiment 1, participants searched for a visible neutral face presented at one of two positions. Prior to the target, a backward-masked and, thus, invisible emotional (fearful/disgusted) or neutral face was presented as a cue, either at target position or away from the target position. If negative emotional faces capture attention in a stimulus-driven way, we would have expected a cueing effect: better performance where fearful or disgusted facial cues were presented at target position than away from the target. However, no evidence of capture of attention was found, neither in behavior (response times or error rates), nor in event-related lateralizations (N2pc). In Experiment 2, we went one step further and used fearful faces as visible targets, too. Thereby, we sought to boost awareness-independent capture of attention by fearful faces. However, still, we found no significant attention-capture effect. Our results show that fearful facial expressions do not capture attention in an awareness-independent way. Results are discussed in light of existing theories.